Production of Paracheirodon innesi on Different Densities in Recirculating System - T. Budiardi; N. Gemawaty; D. Wahjuningrum (Jurnal Akuakultur Indonesia)
The objective of this research was to know production of neon tetra Paracheirodon innesi reared in recirculating system with density 20, 40 and 60 litre-1. Fish with 1.80 ± 0.04 cm lenghts were cultured in 30 x 20 x 20 cm aquarium in recirculating system, during 28 days. Result of this research showed that density of fish rearing affected  survival rate (p0.05) was observed on body lenght, growth of body lenght and coefficient of varians.